PENGARUH VIDEO ANIMASI TERHADAP PENGETAHUAN PERTOLONGAN PERTAMA CEDERA RINGAN PADA SISWA SEKOLAH DASAR - Selpiani, Emerentiana; Fauzan, Suhaimi; Mita, Mita (Jurnal Keperawatan dan Kesehatan, 2025)
Most minor injuries in schools involve bruises, abrasions, lacerations and open wounds, often occurring during sports and recreational activities. Factors such as age, gender and lack of understanding of environmental hazards increase the risk of injury in school-aged children. In addition, lack of knowledge and skills in providing first aid can also exacerbate the severity of the injury. Education through animated videos has been shown to be effective in improving knowledge and positive attitudes towards injuries and first aid. This study aims to determine the effect of animated videos on the knowledge of first aid for minor injuries among elementary school students at SDN 38 Sungai Raya. This study uses quantitative research that uses quasi-experimental methods with One Group planning, pretest and posttest. The sampling method in this study is using the total sampling technique. The research subjects totaled 60 people consisting of 4th and 5th grade students of SDN 38 Sungai Raya. Data were collected by distributing pretest questionnaires, showing animated videos on first aid for minor injuries, and distributing posttest questionnaires. The results of the study obtained an average pretest value of 59.17 and an average posttest value of 80.17. Followed by the wiicoxon test the results of p value = 0.000 ≤ 0.05 which means that there is an effect of increasing the knowledge score of students who are given animated videos and it is hoped that video animation can increase students' knowledge in preventing minor injuries and applying first aid for minor injuries assisted by the school. Keywords: First Aid, Knowledge, Minor Injury, Video animation